Impurities Removal From High Carbon Ferrochromium By Treatment With Slag Mixtures - K. L. Kossyrev; A. V. Pavlov; A. V. Dubachev (The Southern African Institute of Mining and Metallurgy, 2004)
The purpose of the given research was to investigate the possibility of high-carbon ferrochromium refining to remove harmful impurities as a result of metal treatment by slag mixtures on the basis of the CaO-MgO-SiO2system. The final conclusions were drawn from experimental results. It was shown that the treatment of high-carbon ferrochromium by SiO2-MgO-CaO slag mixtures with additions of chromium sinter or iron-ore concentrate removes carbon, sulphur and phosphorus from the metal. A mechanism of phosphorus removal from a melt to a gas phase is proposed.